GENDER, EFIKASI DIRI DAN KARIR FUNGSIONAL GURU PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN JENJANG SEKOLAH DASAR DI JAWA TIMUR - Budiono, Dwi (Hanoman Journal: Physical Education and Sport, 2023)
Gender is thought to influence self-efficacy and career. Objective: find out if there is a relationship between self-efficacy and the functional career of the physical education and sports teacher. This study uses the comparative causal method to look at differences and relationships. The Data were collected through an online questionnaire filled by physical education and sports teachers at elementary school level in East Java and analyzed using the mean test (one Sample T-test) and korelation test. There was no difference in self-efficacy and functional career between male and female teachers and there was no relationship between self-efficacy and functional career in physical education and sports teachers. There is no difference in self-efficacy and functional career between male teachers and female teachers and there is no relationship between self-efficacy and functional career in physical education and sports teachers.